2021
DOI: 10.1177/00220345211018189
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Composites for Biofilms Modulation on Cervical Restorations

Abstract: Cervical composites treating root carious and noncarious cervical lesions usually extend subgingivally. The subgingival margins of composites present poor plaque control, enhanced biofilm accumulation, and cause gingival irritation. A potential material to restore such lesions should combine agents that interfere with bacterial biofilm development and respond to acidic conditions. Here, we explore the use of new bioresponsive bifunctional dental composites against mature microcosm biofilms derived from subging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…We used saliva as an inoculum to grow the multispecies biofilms and establish a more challenging situation for the MagTBO microemulsion. The use of human saliva as inoculum was demonstrated in several studies to provide more clinically relevant biofilms. The saliva mixture collected from 10 individuals can provide a homogeneous bacterial community and allow for analyzing the growth of different bacterial species. Mutans streptococci and lactobacilli were investigated as they are among the leading pathogens in coronal and root caries .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used saliva as an inoculum to grow the multispecies biofilms and establish a more challenging situation for the MagTBO microemulsion. The use of human saliva as inoculum was demonstrated in several studies to provide more clinically relevant biofilms. The saliva mixture collected from 10 individuals can provide a homogeneous bacterial community and allow for analyzing the growth of different bacterial species. Mutans streptococci and lactobacilli were investigated as they are among the leading pathogens in coronal and root caries .…”
Section: Resultsmentioning
confidence: 99%
“…The reported model in this study was not without its limitations. Different studies reported that clinically isolated microorganisms might not recover the same quantity and homogeneity when grown in vitro , as several species could be lost. , Therefore, such a model cannot be relied on to resemble the oral cavity’s microbiota exactly. The same issue is applied when discussing the selective agar media used to isolate and enumerate the bacterial species .…”
Section: Resultsmentioning
confidence: 99%
“…Quaternary ammonium monomers (QAMs) are cationic compounds showing “contact-killing” effects [ 17 , 18 ]. QAMs such as dimethylaminododecyl methacrylate (DMADDM) and dimethylaminohexadecyl methacrylate (DMAHDM) are able to co-polymerize with the resin matrix by the methacrylate groups, and exhibit non-releasing and long-term antimicrobial effects [ 18 , 19 , 20 ] (the molecular structures of DMADDM and DMAHDM were shown in Supplementary Material Figure S1 ). They have been incorporated into dental materials such as composites, adhesives and denture resins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inherent composition of dental adhesives and composites has a high affinity for dental plaque (biofilms) accumulation, leading to the recurrence of cavitation (secondary caries) after the tooth has been restored with these materials [4]. Additionally, resin-based restorative materials are highly susceptible to degradation, which may compromise the strength of such dental restorations over time [5]. As a result, secondary caries and restoration fractures are the most common reasons for the premature failure of dental restorations created with dental adhesives and composites [6] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%